2021
DOI: 10.1111/jocs.15833
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation (ECMO) for critically ill patients with coronavirus disease 2019 (COVID‐19): A retrospective cohort study

Abstract: Purpose: The role of extracorporeal membrane oxygenatio (ECMO) for rescue therapy of respiratory failure in critically ill coronavirus disease 2019 patients remains controversial. We aimed to evaluate the clinical outcomes of ECMO in the treatment of COVID-19 compared with conventional ventilation support. Methods: In this retrospective cohort study, data were collected on extremely critical patients with COVID-19 from January 2020 to March 2020 in intensive care unit of a hospital in charge by national rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…1 , Additional file 1 : Table S4) [ 3 , 5 , 16 65 ]. All studies were retrospective and observational in nature; 22 studies were conducted by studies centres from Europe [ 5 , 17 , 19 , 23 , 27 , 29 , 31 – 34 , 36 , 39 , 42 , 43 , 45 , 46 , 50 , 55 , 56 , 60 , 63 , 65 ], 17 from North America [ 16 , 18 , 20 22 , 24 , 25 , 37 , 40 , 47 , 48 , 52 54 , 57 , 58 , 61 ], 6 from the Asia–Pacific [ 26 , 28 , 35 , 38 , 41 , 44 ], 2 from South-West Asia and Africa,[ 51 , 62 ] 2 from Latin America [ 30 , 64 ], and 3 were studies conducted by centres from multiple ELSO regions [ 3 , 49 , 59 ], of which 2 were based on registry data [ 3 , 49 ]. The pooled age was 52.5 years (95% CI 50.7 to 54.3), and the majority of patients were male (75.0%, 95% CI 72.4% to 77.4%) and obese (BMI: 31.0, 95% CI 30.2 to 31.8).…”
Section: Resultsmentioning
confidence: 99%
“…1 , Additional file 1 : Table S4) [ 3 , 5 , 16 65 ]. All studies were retrospective and observational in nature; 22 studies were conducted by studies centres from Europe [ 5 , 17 , 19 , 23 , 27 , 29 , 31 – 34 , 36 , 39 , 42 , 43 , 45 , 46 , 50 , 55 , 56 , 60 , 63 , 65 ], 17 from North America [ 16 , 18 , 20 22 , 24 , 25 , 37 , 40 , 47 , 48 , 52 54 , 57 , 58 , 61 ], 6 from the Asia–Pacific [ 26 , 28 , 35 , 38 , 41 , 44 ], 2 from South-West Asia and Africa,[ 51 , 62 ] 2 from Latin America [ 30 , 64 ], and 3 were studies conducted by centres from multiple ELSO regions [ 3 , 49 , 59 ], of which 2 were based on registry data [ 3 , 49 ]. The pooled age was 52.5 years (95% CI 50.7 to 54.3), and the majority of patients were male (75.0%, 95% CI 72.4% to 77.4%) and obese (BMI: 31.0, 95% CI 30.2 to 31.8).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (50%) reported data on possible cardiac causes of dea th. 33,34,37,40,45,48,53,54,56,58,59,61,62,71 Overall, a group of 71 patients were identified as dead from cardiac-related causes, such as tamponade, 33,40 heart failure, 37,48,62,69 cardiogenic shock, 69 or cardiac arrest 34 (Table 1).…”
Section: Overall Covid-19 Patient Profilesmentioning
confidence: 99%
“…1 Pontificia Universidad Católica del Ecuador, Quito, Ecuador Universidad de las Américas-Ecuador, Quito, Ecuador Email: aclteran@gmail.com…”
unclassified
“…To the Editor, We have read the article "Extracorporeal membrane oxygenation (ECMO) for critically ill patients with coronavirus disease 2019 (COVID-19): A retrospective cohort study" by Li et al 1 It was felicitous to go through this article, and we hereby applaud the author's efforts. We recognize the conclusion of the study that extracorporeal membrane oxygenation tends to minimize mortality in extremely ill COVID-19 patients compared to the conventional approach.…”
mentioning
confidence: 99%